The relationship between social support and goal pursuit among Chinese college students: The mediating role of just-world beliefs - Chen, Dan; Miao, Xiaolong; Ma, Yuning; Tang, Yulong (Frontiers in Psychology, 2022)
Based on the self-determination theory, this study examined the mechanisms underlying the influence of social support on goal pursuit among college students and focused on the mediating role played by just-world beliefs. The Aspiration Index Scale, Just-World Beliefs Scale and Perceived Social Support Scale were used to assess relationships among 424 college students' just-world beliefs, social support, and goal pursuit; additionally, the underlying mechanisms of those relationships were examined. The results showed that (1) there was a significant positive correlation between social support, just-world beliefs, and goal pursuit; (2) social support had a significant positive influence on goal pursuit; (3) just-world beliefs played a fully mediating role in the influence of social support on goal pursuit, with a mediating effect of 36.38%; and (4) personal just-world beliefs rather than general just-world beliefs fully mediated the effect of social support on goal pursuit, with a mediating effect of 39.00%. In conclusion, we found that for Chinese college students, social support has a significant positive effect on goal pursuit, and personal just-world beliefs play a fully mediating role in the effect of social support on goal pursuit.